2010
DOI: 10.1111/j.1462-2920.2010.02392.x
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal tag pyrosequencing of DNA and RNA from benthic coral reef microbiota: community spatial structure, rare members and nitrogen‐cycling guilds

Abstract: Ribosomal tag libraries based on DNA and RNA in coral reef sediment from Hawaii show the microbial community to be dominated by the bacterial phyla Proteobacteria, Firmicutes and Actinobacteria, the archaeal order Nitrosopumilales and the uncultivated divisions Marine Group III (Euryarchaeota) and Marine Benthic Group C (Crenarchaeota). Operational taxonomic units (OTUs) number in the high thousands, and richness varies with site, presence or absence of porewater sulfide (sediment depth), and nucleotide pool. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
84
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 126 publications
8
84
0
2
Order By: Relevance
“…Historically, rRNA analyses have been used to quantify populations' growth rates in mixed microbial communities (for example, Poulsen et al, 1993;Muttray et al, 2001), but recent application has shifted toward the more qualitative approach using rRNA to identify currently active microbial populations in a mixed community (for example, Jones and Lennon, 2010;Kamke et al, 2010;Campbell et al, 2011;DeAngelis et al, 2011;Gaidos et al, 2011;Reid et al, 2011;Baldrian et al, 2012;Mannisto et al, 2012;Mattila et al, 2012;Simister et al, 2012;Campbell and Kirchman, 2013;Hunt et al, 2013;Yarwood et al, 2013). Two principal lines of evidence used to support rRNA as an indicator of current activity originate from earlier studies testing how rRNA scales with growth rate.…”
Section: Rrna and Its Use In Microbial Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, rRNA analyses have been used to quantify populations' growth rates in mixed microbial communities (for example, Poulsen et al, 1993;Muttray et al, 2001), but recent application has shifted toward the more qualitative approach using rRNA to identify currently active microbial populations in a mixed community (for example, Jones and Lennon, 2010;Kamke et al, 2010;Campbell et al, 2011;DeAngelis et al, 2011;Gaidos et al, 2011;Reid et al, 2011;Baldrian et al, 2012;Mannisto et al, 2012;Mattila et al, 2012;Simister et al, 2012;Campbell and Kirchman, 2013;Hunt et al, 2013;Yarwood et al, 2013). Two principal lines of evidence used to support rRNA as an indicator of current activity originate from earlier studies testing how rRNA scales with growth rate.…”
Section: Rrna and Its Use In Microbial Ecologymentioning
confidence: 99%
“…Ribosomal RNA genes (rRNA genes) are frequently used to identify microorganisms present in environmental samples regardless of metabolic state, while ribosomal RNA (rRNA) has been widely applied to characterize the growing or active microbes. We found 4100 studies that used rRNA for these purposes, including recent studies using rRNA to identify currently active microbes (for example, Muttray and Mohn, 2000;Duineveld et al, 2001;Mills et al, 2005;Schippers et al, 2005;Gentile et al, 2006;DeAngelis et al, 2010;Jones and Lennon, 2010;Brettar et al, 2011;Egert et al, 2011;Gaidos et al, 2011;Wü st et al, 2011;Mannisto et al, 2012;Hunt et al, 2013). However, conflicting patterns between rRNA content and growth rate indicate that rRNA is not a reliable metric for growth or activity and in some cases may be grossly misleading.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies that have used rRNA to characterize the growing or active microbes. For example, Blazewicz et al (2013) found >100 studies that used rRNA for these purposes, including recent studies using rRNA to identify currently active microbes (e.g., Gentile et al 2006;DeAngelis et al 2010;Jones and Lennon 2010;Gaidos et al 2011;Lanzen et al 2011;Wust et al 2011;Brettar et al 2012;Mannisto et al 2013). However, Blazewicz et al (2013) argued that there are conflicting patterns between rRNA content and growth rate, indicating that rRNA is not a reliable metric for growth or activity, and suggested instead to employ rRNA abundance data as an index of potential activity that provides the basis for further investigations.…”
Section: Proteobacteriamentioning
confidence: 99%
“…It is often suggested that cellular rRNA concentrations are correlated with growth rate and activity, hence rRNA may reflect which members of the community are active (Kamke et al, 2010). To explore whether these 'sponge-specific' bacteria were metabolically active outside of their host we examined the only ICoMM study to have included both RNA-and DNA-derived samples (Coral Reef Sediment, (CRS); Gaidos et al, 2011). Of the sponge-specific and sponge-coral-specific clusters identified in the CRS study, 25 contained CRS sequences found only in DNA-derived samples, 9 contained sequences in both DNA-and RNA-derived samples and only 1 contained sequences exclusively from RNA-derived samples.…”
mentioning
confidence: 99%